Geriatric nutritional risk index as a predictor of 30-day and 365-day mortality in patients with acute myocardial infarction: a retrospective cohort study using the MIMIC-IV database - Zheng, Xiaolong; Zheng, Xin; Zhang, Changgui; Liu, Minghua (Frontiers in Nutrition, 2025)
BackgroundThe Geriatric Nutritional Risk Index (GNRI) is a clinical indicator for evaluating the nutritional status of patients, but its role in the short-term prognosis of patients with acute myocardial infarction is still not fully understood. This study aims to explore the correlation between the GNRI and the overall mortality within 30 days and 365 days in those with acute myocardial infarction (AMI).MethodsA retrospective analysis was performed utilizing the Medical Information Mart for Intensive Care IV (MIMIC-IV) database. The study included 895 patients diagnosed with AMI and identified through ICD9 and ICD10 codes (410, I21, I23) who were hospitalized for the first time due to AMI. Subjects were classified into four groups according to GNRI: high (GNRI <82, n = 110), moderate (82 ≤ GNRI <92, n = 205), low (92 ≤ GNRI <98, n = 225), and no nutritional risk (GNRI ≥98, n = 355). Restricted cubic splines (RCS) and threshold effect analyses were applied to explore the non-linear relationship between GNRI and mortality. Subgroup analyses were conducted based on gender, hypertension, diabetes, stroke, hyperlipidemia, chronic obstructive pulmonary disease, and age. A mediation study was conducted to investigate the impact of lymphocytes on the association between GNRI and mortality.ResultsIn an overall sample of 895 patients, an elevated GNRI correlated with reduced 30-day (HR = 0.937, 95% CI: 0.917–0.957, p < 0.001) and 365-day mortality (HR = 0.937, 95% CI: 0.923–0.950, p < 0.001). The trend analysis for GNRI categories indicated a significant decline in mortality associated with rising GNRI (P for trend <0.001). Subgroup analysis validated the consistency of such results throughout diverse patient characteristics. The lymphocytes significantly mediated the relationship between GNRI and 30-day mortality (ACME: 0.022, 95% CI: 0.003–0.180, p < 0.001). A landmark analysis at 20 days after admission further demonstrated the impact of GNRI on mortality during different phases of recovery.ConclusionThis study highlights the prognostic value of GNRI in predicting short-term and long-term mortality in AMI patients, emphasizing the significance of nutritional status and inflammatory indicators in the therapy and risk assessment of these individuals.